Erythrocytes in the endocardial structures of embryonic heart - Mashtalir M.A.; Lapsar A.S. (Морфологія, 2009)
With the purpose to study the phenomenon of erythrocyte migration into the endocardial structures of the embryo heart the serial sections of chick embryos of white leghorn and Cobb 500 cross on 68, 72, 76, 80 and 96 hours of incubation were studied in light microscope. Erythrocytes, freely arranged in the cardiac jelly of conotrunkal cushions, were a frequent finding on 72 hours (stage 20 by V.Hamburger, H.L.Hamilton, 1951). Endocardially disposed erythrocytes were adjoined to transformed endothelial cells which started to migrate into the cardiac jelly. Morphological pictures show that erythrocytes migrate via diapedesis through endocardail endothelium. Erythrocytes were also encountered distant from endocardium, sometimes close by the myocardium of conotrunkal region. These erythrocytes may get to the cardiac jelly by another way. The pictures of deformation of erythrocytes observed in the cardiac jelly show the further dying of these cells. If the incubation time was less than 72 hours, and later, on 76 and 80 hours of incubation, erythrocytes were rarely found in the cardiac jelly of endocardial cushions. We consider the investigated phenomenon is determined by a transient, expected in certain stages, status of endocardial endothelial cells, which may relate with epithelial-mesenchymal transformation.